Individualized lipid profile in urine-derived extracellular vesicles from clinical patients with Mycobacterium tuberculosis infections - Lyu, Lingna; Jia, Hongyan; Liu, Qiuyue; Ma, Wenxia; Li, Zihui; Pan, Liping; Zhang, Xiuli (Frontiers in Microbiology, 2024)
Background: Lipids are a key nutrient source for the growth and reproduction of Mycobacterium tuberculosis (Mtb). Urine-derived extracellular vesicles (EVs), because of its non-invasive sampling, lipids enrichment, specific sorting character, have been recognized as a promising research target for biomarker discovery and pathogenesis elucidation in tuberculosis (TB). We aim to profile lipidome of Mtb infected individuals, offer novel lipid signatures for development of urine-based TB testing, and provide new insights into the lipid metabolism after Mtb infection. Methods: Urine-derived extracellular vesicles from 41 participants (including healthy, pulmonary tuberculosis, latent tuberculosis patients and other lung disease groups) were isolated and individually detected using targeted lipidomics and proteomics technology platforms. Biomarkers were screened by multivariate and univariate statistical analysis and evaluated by SPSS software. Correlation analyses were performed on lipids and proteins using the R Hmisc package. Results: Overall, we identified 226 lipids belonging to 14 classes. Of these, 7 potential lipid biomarkers for TB and 6 for latent TB infection (LTBI) were identified, all of which were classified into Diacylglycerol(DAG), Monoacylglycerol(MAG), Free fatty acid(FFA) and Cholesteryl ester(CE). Among them, FFA(20:1) was the most promising biomarker target in diagnosing TB/LTBI from other compared groups, and also have great diagnostic performance in distinguishing TB from LTBI with AUC of 0.952. Besides, enhanced lipolysis happened as early as individuals got latent Mtb infection, and ratio of raft lipids were gradually elevated along TB progression. Conclusion: This study demonstrated individualized lipids profile of urinary EVs in patients with Mtb infection, revealed novel potential lipid biomarkers for TB/LTBI diagnosis and explored mechanisms by which EVs lipid raft-dependent bio-processes might affect pathogenesis. It lays a solid foundation for the subsequent diagnosis and therapeutic intervention of TB.